2020
DOI: 10.1158/0008-5472.can-19-1764
|View full text |Cite
|
Sign up to set email alerts
|

MAFB Promotes Cancer Stemness and Tumorigenesis in Osteosarcoma through a Sox9-Mediated Positive Feedback Loop

Abstract: Transcription factors MAFB and Sox9 form a positive feedback loop to maintain cell stemness and tumor growth in vitro and in vivo, revealing a potential target pathway for therapeutic intervention in osteosarcoma.. Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Currently, the association of SOX10 [52] , MDM4 [53] , MAPK8 [54] , MDM2 [55] , CDK4 [56] , CCND3 [57] , Runx2 [58] , Gli1 [59] , FRS2 mutation [55] with osteosarcoma formation has been documented, while no report is so far available concerning GPC3 mutation and expression in osteosarcomas especially those with metastasis and/or multidrug resistance. It has been found that GPC3 is an oncofetal protein expressed in 72% of hepatocellular carcinomas [60] and 97% in hepatoblastomas [59] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the association of SOX10 [52] , MDM4 [53] , MAPK8 [54] , MDM2 [55] , CDK4 [56] , CCND3 [57] , Runx2 [58] , Gli1 [59] , FRS2 mutation [55] with osteosarcoma formation has been documented, while no report is so far available concerning GPC3 mutation and expression in osteosarcomas especially those with metastasis and/or multidrug resistance. It has been found that GPC3 is an oncofetal protein expressed in 72% of hepatocellular carcinomas [60] and 97% in hepatoblastomas [59] .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of MAFB expression in ovarian cancer cells inhibited their proliferation and invasion capacities, similar to that observed after RecQL4 suppression. Recent evidence points out a role of MAFB in osteosarcoma by promoting cancer stemness and tumor aggressiveness [Chen et al, 2020]. It is likely that RecQL4 exerts its effect on cancer stemness through a positive regulation of MAFB.…”
Section: Recql4 Protects Cancer Cells From Endogenous and Exogenous Dna Damagementioning
confidence: 99%
“…Previous studies provided experimental evidence for the indirect roles of RecQL4 in cancer cell invasion and metastasis [Chen et al, 2020;Guo et al, 2020;Lu et al, 2020;Machlowska et al, 2020]. Su et al [2010] provided the first evidence that RecQL4 suppression reduced the human prostate cancer cell invasion in vitro and tumor growth of mouse xenografts in vivo.…”
Section: Recql4 Contributes To Cancer Cell Survival Invasion and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…The MAF TFs regulate gene expression and differentiation in a wide variety of tissues and are also involved in human diseases, including tumorigenesis (17,18). There are five MAF TFs in human cells: MAFA, MAFB, MAFF, MAFG, and MAFK.…”
Section: Introductionmentioning
confidence: 99%